STUDY OF INTRATESTICULAR INTRODUCTION’s INFLUENCE OF STEM CELLS’ CULTURE ON THE STATE OF THE INVESTIGATED RATS ON BACKGROUND OF THEIR DEFEAT OF BICHLORIDE CADMIUM - Antonyan, I.M. (World of Medicine and Biology, 2012)
In the article are results of the experiments as for effectiveness stem cells culture (SCC) using for the secondary androgen deficiency (SAD) treatment at rats males. The result of the experiment had shown that the quantity of SCC 200000 in the every testicle had come to the improvement of the hormonal status of animals. This quantity of the SCC had come to the regeneration of the morphological and morphometrical characteristics of the animal’s testicles tissue.